KARAKTERISASI DAN INDEKS GLIKEMIK BERAS ANALOG BERBAHAN DASAR TEPUNG JAGUNG - Kurniawati, Maya; Budijanto, Slamet; Yuliana, Nancy Dewi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The aim of this study was to obtain the most optimum rice analogue formulation made from corn, sago, soybean, and rice brans. DX7 Mixture Design program was used to achieve the purpose. Antioxidant and lightness were used as the analysis response. The rice was then characterized for physical and chemical properties, antioxidant activity, and glycemic index. The most optimum rice analogue formulation based on the value of antioxidant and brightness parameters consisted of 32.17% corn flour, 16.67% sagoo flour, 13.3% soybean flour, rice brans 3.16%, and 1.33% GMS (the water added was 50% of the amount of the dough). The formulation showed that the rice analogue was potential to be developed into a functional food that supplies fiber 13.30% (> 6.00%), had low glycemic index (54±18) with 28.02%. amylose , contained bioactive components that acts as antioxidants, such as α-tocopherols 1.00% and ϒ-oryzanol, 48.70%.Keywords: antioxidant, glicemic index, oryzanol, rice analog, tocopherol